The “Movement and Rest” in Gospel of Thomas 50 - LENSINK, Benjamin (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
The fiftieth logion of the Gospel of Thomas is an enigmatic triad of questions and answers told by Jesus to his disciples. The answer to the third question “What is the sign of your (pl) Father which is in you (pl)?” reads “it is movement and rest.” This phrase has no known parallels in similar literature and its meaning is unclear. The current article evaluates different explanations offered in recent scholarship before assessing the words “movement” and “rest” in the Gospel of Thomas as a whole. It then gives an overview of four possible contexts: Genesis, Jewish Hermeticism, Platonism, and Aristotelianism. The article concludes with claiming that a Platonist view makes most sense: Just as the Demiurge in Plato’s Timaeus placed the rotating soul – which moves while staying at rest – into the head of humankind, so the sign of the Father in his elect disciples is movement and rest.